Effect of Skin Contact Before and During Alcoholic Fermentation on the Chemical and Sensory Profile of South African Chenin Blanc White Wines - Aleixandre-Tudo, J.L.; Weightman, C.; Panzeri, V.; Nieuwoudt, H.H.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2016)
The volatile and phenolic composition of Chenin blanc wines made with different skin contact treatments was studied. One batch of grapes was used to make a dry white wine according to two different treatments, namely pre-fermentative skin contact and complete fermentation on the skins. A white wine fermented without any skin contact was used as control. Fermentation on the skins and skin contact before fermentation led to significantly lower levels of terpenes, esters, acids and thiols, and the highest significant levels of alcohols and phenolic compounds. However, this effect was less pronounced in wines with skin contact before fermentation. Sensory analysis of all the experimental wines was also performed. The results showed a significant shift from the sensory attributes of fresh and tropical fruits of the control Chenin blanc wines towards riper fruit notes in the skin contact treatments. This observation was correlated with the length of the skin contact period. Possible reasons to explain the results observed in this study are discussed.